Chiral dialkyl ditellurides: Conformation of chiral chromophore by circular dichroism and DFT calculation. Issue 10 (3rd August 2017) - Ścianowski, Jacek; Pacuła, Agata J.; Skowronek, Paweł
Abstract: The twisted structure of ditellurides, in a similar way as in other dichalcogenes, leads to different absorption of circularly polarized light by quasi‐enantiomeric chiral orbitals. Chiral optically active ditellurides are not common compounds and this phenomenon is not widely reported. As chiral ditellurides found an application in asymmetric synthesis, their molecular structure, understood as their conformation, became an important factor for understanding their reactivity. Until now there are few examples of chiral ditellurides known and their structure was not analyzed in details. This article presents the results of our most recent research on the structure of chiral ditellurides investigated by electronic circular spectroscopy (ECD) supported by quantum‐chemical calculation. This enables us to suggest a relationship between chirality of alkyl substituent and chirality (conformation) of ditelluride. Abstract :